PROFESSIONAL AND TECHNOLOGICAL EDUCATION: A SUCCINCT ANALYSIS OF THE TRAJECTORY OF THE GENDER FEMALE (Interdisciplinary Studies Journal, 2024)
The article succinctly discusses the female trajectory in Brazilian educational history, essentially in Professional and Technological Education. In this context, it problematizes the gender disparities that have been historically constructed in the educational sphere and in Professional and Technological Education (EPT), with positions “fated” to women during professional training. Thus, from this brief historical narrative we can see the resistance of historical prototypes of sexual distinction in school and professional training and the restriction, even if representative, of the male sphere to the detriment of the female universe. The objectives of this article are agreed with the extension of discussions about gender in Professional Education based on a bibliographical review on female education at different moments in the history of Brazil.
Keywords: Women's Education; Professional and Technological Education; Gender Inequality